Current differentiation between radiographic and non-radiographic axial spondyloarthritis is of limited benefit for prediction of important clinical outcomes: data from a large, prospective, observational cohort. Issue 1 (2nd February 2022) - Ciurea, Adrian; Kissling, Seraphina; Bürki, Kristina; Baraliakos, Xenofon; de Hooge, Manouk; Hebeisen, Monika; Papagiannoulis, Eleftherios; Exer, Pascale; Bräm, René; Nissen, Michael J; Möller, Burkhard; Kyburz, Diego; et al.
Abstract : Objective: To compare disease characteristics and outcomes between patients with axial spondyloarthritis with non-radiographic disease (nr-axSpA), bilateral grade 2 sacroiliitis (r22axSpA) and unilateral/bilateral grade 3–4 sacroiliitis (r3+axSpA) according to the modified New York criteria. Methods: We included patients with axial spondyloarthritis with available pelvic radiographs from the Swiss Clinical Quality Management Cohort. Retention of a first tumour necrosis factor inhibitor (TNFi) was investigated with multiple adjusted Cox proportional hazards models. The proportion of patients reaching 50% reduction in the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI50) at 1 year was assessed with multiple adjusted logistic regression analyses. Spinal radiographic progression, defined as an increase in ≥2 mSASSS units in 2 years, was assessed in generalised estimating equation models. Results: From 2080 patients, those with nr-axSpA (n=485) and r22axSpA (n=443) presented with lower C reactive protein levels and less severe clinical spinal involvement compared with patients with r3+axSpA (n=1152). While TNFi retention was similar in r22axSpA and nr-axSpA, the risk of discontinuation was significantly lower in r3+axSpA (HR 0.60, 95% CI 0.44 to 0.82 vs nr-axSpA). BASDAI50 responses at 1 year were comparable in r22axSpA and nr-axSpA, with a better response associated with r3+axSpA (OR 2.05, 95% CI 1.09 to 3.91 vs nr-axSpA). Spinal radiographic progression was similar in r22axSpA and nr-axSpA and significantly higher in r3 +axSpA. Conclusion: Patients with r22axSpA are comparable to nr-axSpA patients but differ from patients with more severe sacroiliac damage with regard to treatment effectiveness and spinal radiographic progression. Therefore, current differentiation between nr-axSpA and radiographic disease seems of limited use for outcome prediction.